PROMOTING CESSATION AND A TOBACCO FREE FUTURE: KNOWLEDGE AND ATTITUDE OF PHARMACY STUDENTS REGARDING SMOKING CESSATION IN A NIGERIAN UNIVERSITY (2022)
Tobacco smoking is a global public health threat and the largest single driver of health inequalities. Currently, there are over a billion smokers worldwide with approximately 80% of the smokers living in low-and-middle-income countries like Nigeria. Knowledge gaps on smoking cessation among pharmacy students might impact the quality of service these future pharmacists would provide in practice. Therefore, this study aimed to evaluate the knowledge and attitude of pharmacy students regarding smoking cessation in a Nigerian university. A University-based cross-sectional study was conducted among 277 pharmacy students of a Nigerian university using a pretested self-administered questionnaire between August and December 2019. Data were summarised descriptively using IBM SPSS (version 23). Most of the pharmacy students 203 (73.2%) agreed it is the pharmacists’ responsibility to support patients with smoking cessation. The majority of our respondents 226 (81.6%) reported pharmacy students need more training on smoking cessation. Thirty-three (11.9%) pharmacy students knew nicotine does not cause cancer. Less than one-tenth 27 (9.7%) of the pharmacy students were aware of smoking cessation products. Overall, 203 (73.2%) respondents had poor knowledge (score < 60%) and an average positive attitude about smoking cessation. Pharmacy students have suboptimal knowledge about smoking cessation. However, they revealed a positive attitude towards smoking cessation. Therefore, there is a need for educational interventions to address the deficit in smoking cessation knowledge, as well as equip future healthcare providers. Thus, improving the quality of public health especially among smokers in Nigeria.